Effect of Low Temperature on Electrochemical Performance of Polyanion Battery Material. Issue 1 (1st December 2022) - He, Rui; Wei, Aijia; Bai, Xue; Li, Xiaohui; Mu, Jinping; Liu, Peng; Liu, Zhenfa; Zhang, Lihui
Abstract: In this paper, we prepared LiFePO4/C by the solid-state method. For the sake of discussing the function of low temperature on material performance, we analyzed the microstructure of materials using X-ray diffraction and scanning electron microscopy. Also, we conducted charge/discharge tests, rate performance, and electrochemical impedance performance to study the electrochemical performances. Our conclusion revealed that the charge transfer impedance increases obviously when the temperature drops, this will leads to a sharp decline in the electrochemical performance of the material.